Diagnóstico da oferta de indicadores bibliométricos nas bibliotecas das universidades públicas do estado de São Paulo - Ramos, Renan Carvalho (2018)
The general objective of this thesis is to understand the offer and the capacity to provide bibliometric services in the libraries of public universities of the state of São Paulo. Literature review was elaborated on bibliometric and its main indicators as products to measure science and scientific performance. For the realization of this research were necessary the use of combinations of data collection procedures, namely: document analysis, bibliometric analysis and application of interviews to allow the elaboration of a vision on the provision of bibliometric services in academic libraries. The results presented bibliometrics as a field of research in development and growth around the world; his presence as an activity and research in the Brazilian academic libraries; his approach in the courses of Library and Information Science in Brazil and finally the analysis of the library systems managers on the offer of bibliometric services. With the results of this research it is expected to contribute to understanding the scenery and the perception of academic libraries facing the demands of their community for these products. In addition, the results may allow the preparation of proposals for academic libraries to offer bibliometric services to their users.